2014
DOI: 10.1007/s13592-014-0340-z
|View full text |Cite
|
Sign up to set email alerts
|

Visitation and gnawing behaviour of Japanese honeybee Apis cerana japonica to lettuce

Abstract: -The Japanese honeybee, Apis cerana japonica , is regarded as an important pollinator of crops and wild flowers. On the other hand, its gnawing behaviour on lettuce Lactuca spp. results in serious damage to the crop yield. Little is known about the gnawing behaviour of A. c. japonica . In the present study, field experiments were conducted to clarify the seasonality of this behaviour and the preference of A. c. japonica toward lettuce. The rates of lettuce damage by gnawing differed among furrows, and the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Overall, our study revealed a close relationship between the previously reported leaf-gnawing behaviour of A. cerena (Yokoi 2005(Yokoi , 2015 and the occurrence of dark-coloured stains around the entrances to the hives of these bees (Okada 1997;Sasaki 1999). The purpose of this behaviour is presumably to prevent mass attack by giant hornets.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Overall, our study revealed a close relationship between the previously reported leaf-gnawing behaviour of A. cerena (Yokoi 2005(Yokoi , 2015 and the occurrence of dark-coloured stains around the entrances to the hives of these bees (Okada 1997;Sasaki 1999). The purpose of this behaviour is presumably to prevent mass attack by giant hornets.…”
supporting
confidence: 86%
“…Another A. cerana behaviour thought to be a defensive strategy to prevent predation by V. mandarinia is 'entrance smearing' with unknown materials, as suggested by Okada (1997) and Sasaki (1999). The use of plant materials other than pollen or nectar by A. cerana for non-nutritional purposes has not yet been demonstrated; A. cerana has been reported to gnaw leaves at the centre of green head lettuce (Yokoi 2005(Yokoi , 2015 in autumn. Here, we report the plant-gnawing behaviour of A. cerana attributable to the collection of plant materials used to smear around the hive entrance, leaving dark-coloured stains similar to those described by Okada (1997) and Sasaki (1999).…”
mentioning
confidence: 99%
“…c . japonica has been reported to gnaw on leaves and has been found at the centers of heads of green lettuce (Yokoi , ). However, it is not clear why A .…”
Section: Results Of Attack Simulation Experiments Carried Out From 21mentioning
confidence: 99%
“…This is the only report of a honeybee species chewing sepals and petals and thus destroying a flower. There is one publication on honeybees feeding on vegetative parts of plants (not on tepals) by Yokoi (2015). Worker bees of A. c. japonica feed on leaves of cultivated lettuce and, in addition, of several Asteracea plants.…”
mentioning
confidence: 99%